IPS USM Guide Book: A Guide to the preparation submission and examination of Thesis - IPS, Institut Pengajian Siswazah (Institut Pengajian Siswazah, 2010)
This guidebook describes in detail the procedures and format which your thesis must fulfil before the final submission. Throughout this document, the word “thesis” is used broadly to refer to either MastersTheses or PhD Dissertations. As you begin to prepare your thesis following the guidelines given, we would like to emphasize that Universiti Sains Malaysia upholds the policy of ensuring all candidates for higher degrees are trained to practice highest standards of intellectual honesty and integrity. This means that ideas and data of other researchers that you used must be duly acknowledged in your thesis by citing the quoted materials and providing the full references in the reference list. Failure to do this will make you liable for plagiarism. Please remember that a writer may unconsciously commit plagiarism but nonetheless it does not absolve him/her from the charge.